2002
DOI: 10.1006/viro.2002.1760
|View full text |Cite
|
Sign up to set email alerts
|

The N-linked Glycan g15 within the V3 Loop of the HIV-1 External Glycoprotein gp120 Affects Coreceptor Usage, Cellular Tropism, and Neutralization

Abstract: We have studied infectivity and neutralization of X4, R5, and R5X4 tropic HIV-1 mutants, which are lacking N-linked glycosylation sites for glycans g13, g14, g15, and g17 in the V3 loop region of gp120. X4-tropic NL4-3 mutants lacking combinations of g14/15 or g15/17 showed markedly higher infectivity in CXCR4-specific infection. The role of g15 in CCR5-specific infection was investigated using viruses with high (NL-918, R5-monotropic), medium (NL-991, R5-monotropic), and low (NL-952, R5X4-dualtropic) CCR5-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 53 publications
(67 reference statements)
4
103
1
Order By: Relevance
“…Genotypic prediction of viral tropism based on the PSSM method of Jensen et al (21) correlated with the phenotypic tropism assigned to the virus for all clones from patient A and 11/12 unique V3 loop sequences of Env clones from patient C. However, in patient B, the PSSM scores failed to predict CXCR4 usage in all but three sequenced clones assigned a CXCR4-tropic phenotype. Instead, the loss of the g15 N-linked glycosylation site (amino acids 6 to 8), reported to enable more efficient use of CXCR4 (34) and observed in all 28 CXCR4-using clones, appeared to be the most reliable genotypic predictor of CXCR4 usage in this patient.…”
Section: Vol 80 2006 Emergence Of Cxcr4-using Virus On Maraviroc Thmentioning
confidence: 77%
See 1 more Smart Citation
“…Genotypic prediction of viral tropism based on the PSSM method of Jensen et al (21) correlated with the phenotypic tropism assigned to the virus for all clones from patient A and 11/12 unique V3 loop sequences of Env clones from patient C. However, in patient B, the PSSM scores failed to predict CXCR4 usage in all but three sequenced clones assigned a CXCR4-tropic phenotype. Instead, the loss of the g15 N-linked glycosylation site (amino acids 6 to 8), reported to enable more efficient use of CXCR4 (34) and observed in all 28 CXCR4-using clones, appeared to be the most reliable genotypic predictor of CXCR4 usage in this patient.…”
Section: Vol 80 2006 Emergence Of Cxcr4-using Virus On Maraviroc Thmentioning
confidence: 77%
“…V3 loop sequences of clones were also analyzed to predict CXCR4 coreceptor usage on the basis of the PSSM (http://ubik.microbiol.washington.edu/computing /pssm/) (21), the loss of the g15 N-linked glycosylation site (amino acids 6 to 8) (34), and the presence of basic amino acid residues at positions 11 and/or 25 (8,14,20). The results of these genotypic analyses were compared to the coreceptor tropism assigned to the individual Env clones from the phenotypic assay described above.…”
Section: Methodsmentioning
confidence: 99%
“…One of these, the V3 loop, elicits neutralizing anti-HIV antibodies and has been a target for HIV vaccine development [1]. It has been shown that carbohydrates within and around the V3 loop shield binding sites for the chemokine receptors, and loss of these carbohydrates increases infectivity [2][3][4]. The Nlinked glycans on this loop have been reported to strongly influence coreceptor usage, with CCR5 being used during the early stages of disease and CXCR4 being used as the disease progresses [3,4].…”
Section: H Uman Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…However, it would be relatively easy to design CS-PCR for any target codon of interest -for example, monitoring the loss of N-linked glycosylation sites associated with coreceptor utilization. 22,23 An additional constraint is that CS-PCR was specifically designed for subtype B. Additional primers would be needed to test other subtypes.…”
Section: Discussionmentioning
confidence: 99%